Gigantic Calculi in Continent Urinary Diversion - Siddalingeshwar Neeli; Sree Harsha Nutalpati; Manas Sharma (Journal of Urological Surgery, 2020)

(untitled)
Continent urinary reservoirs are safe and accepted modes of urinary diversion in selected patients. However, they are associated with long-term complications such as recurrent pyelonephritis, metabolic acidosis, urolithiasis and stomal problems. We are reporting a patient who had undergone continent urinary diversion for the treatment of extrophy of the bladder and presented ten years later with formation of large pouch calculi and infection. The calculi were successfully retrieved by pouchotomy. The combined weight of the stones was 1,254 gms. To the best of our knowledge, this is the largest stone burden in continent urinary diversion reported in literature.